Symptomatic bilateral coronary artery fistula to pulmonary artery in elderly patient - Pereira da Silva, F (2016)
We report the imaging findings of an uncommon coronary vascular termination anomaly, with fistula to the pulmonary artery. This 70 year old female patient presented unstable angina, showing a coronary artery fistula depicted in coronary angiogram from the left coronary to the pulmonary artery, with no significant atherosclerotic pathology. Due to development of ventricular tachycardia in stress echocardiogram examination, she was proposed for coronary fistula closure. Coronary CT was performed for procedure planning and allowed the identification of a second unsuspected fistula from the right coronary to the right pulmonary artery. Congenital coronary anomalies are a possible cause of symptomatic coronary pathology in patients of any age. In older patients, coronary artery fistulas are rare, especially when symptomatic. Adequately performed CT examinations, using its post processing capabilities, with 3D and MIP reconstructions are invaluable in delineating coronary anatomy, essential for further treatment planning.